Why Are Some Women Empowered While Others Are Not? - Ahmed, Akhter; Sufian, Farha (2018)
Using two survey rounds of IFPRI's Bangladesh Integrated Household Survey (BIHS), IFPRI researchers under the USAID-funded Policy Research and Strategy Support Program (PRSSP) analyze women's empowerment dynamics from 2011/12 to 2015, as well as examine risk factors that may explain why some women remain chronically disempowered.